Development and In Vitro/Ex Vivo Evaluation of Lecithin-Based Deformable Transfersomes and Transfersome-Based Gels for Combined Dermal Delivery of Meloxicam and Dexamethasone. (29th November 2022) - Khan, Muhammad Imran; Yaqoob, Samiya; Madni, Asadullah; Akhtar, Muhammad Furqan; Sohail, Muhammad Farhan; Saleem, Ammara; Tahir, Nayab; Khan, Kashif-ur-Rehman; Qureshi, Omer Salman
Abstract : Transfersomes (TFS) are the promising carriers for transdermal delivery of various low and high molecular weight drugs, owing to their self-regulating and self-optimizing nature. Herein, we report synthesis and characterization of TFS loaded with meloxicam (MLX), an NSAID, and dexamethasone (DEX), a steroid, for simultaneous transdermal delivery. The different formulations of TFS containing varying amounts of lecithin, Span 80, and Tween 80 (TFS-1 to TFS-6) were successfully prepared by thin-film hydration method. The size of ranged between 248 and 273 nm, zeta potential values covering from –62.6 to –69.5 mV, polydispersity index (PDI) values in between 0.329 and 0.526, and entrapment efficiency of MLX and DEX ranged between 63-96% and 48-81%, respectively. Release experiments at pH 7.4 demonstrated higher cumulative drug release attained with Tween 80 compared to Span 80-based TFS. The scanning electron microscopy (SEM) of selected formulations -1 and TFS-3 revealed spherical shape of vesicles. Furthermore, three optimized transfersomal formulations (based on entrapment efficiency, TFS-1, TFS-3, and TFS-5) were incorporated into carbopol-940 gels coded as TF-G1, TF-G3, and TF-G5. These transfersomal gels were subjected to pH, spreadability, viscosity, homogeneity, skin irritation, in vitro drug release, and ex vivo skin permeation studies, and the results were compared with plain (nontransfersomal) gel having MLX and DEX. TFS released 71.72% to 81.87% MLX in 12 h; whereas, DEX release was quantified as 74.72% to 83.72% in same time. Nevertheless, TF-based gels showed slower drug release; 51.54% to 59.60% for MLX and 48.98% to 61.23% for DEX. The TF-G systems showed 85.87% permeation of MLX (TF-G1), 68.15% (TF-G3), and 68.94% (TF-G5); whereas, 78.59%, 70.54%, and 75.97% of DEX was permeated by TF-G1, TF-G3, and TF-G5, respectively. Kinetic modeling of release and permeation data indicated to follow Korsmeyer-Peppas model showing diffusion diffusion-based drug moment. Conversely, plain gel influx was found mere 26.18% and 22.94% for MLX and DEX, respectively. These results suggest that TF-G loaded with MLX and DEX can be proposed as an alternate drug carriers for improved transdermal flux that will certainly increase therapeutic outcomes.